China starts trading carbon - Ellermann, C; Boning, C (Oxford Institute for Energy Studies, 2014)
China has been the world’s largest emitter of greenhouse gases (GHGs) for several years now, per capita emissions have almost reached the European average, and its share of global energy use and GHG emissions keeps rising steadily. By introducing emissions trading scheme (ETS) pilots in five cities and two provinces, China has been indicating bold reforms in its governance of energy and the environment. Handing over the allocation of greenhouse gas pollution rights to markets, the government of China is signalling to the international community that it intends to be compared to Europe and progressive regions in North America when it comes to adjusting its economy to a carbon-constrained future.